Microclimate-based mortality analysis of the Cibodas Botanic Gardens plant collection - IMAWAN WAHYU HIDAYAT; DIDIK WIDYATMOKO (Universitas Syiah Kuala, 2021)
Despite the routinely conducted treatment and maintenance of garden plant collection, the monthly mortality figures of the Cibodas Botanic Gardens (CBG) plant collections remain significant. It is presumed that the microclimate has a crucial influence on plant survivorship in the field. This study aimed to analyze the effect of microclimate conditions on the mortality rate of the CBG plant collection. The study was conducted by correlating the number of mortal plants with CBG monthly microclimatic conditions from 2017 to 2018. The analyzed microclimate parameters were temperature, relative humidity, precipitation, wind velocity, and solar radiation. The multiple regression modeling, t-test, and Pearson correlation test (r) were utilized to measure the level of significance of the correlation (α = 0.05). The findings were shown that the maximum wind velocity was the primary unit correlated to the number of mortality. The correlation was strong positive (r = 68.8%), and significant (p-value α). We suggested anticipating the disadvantages influences of strong wind supported by other extreme microclimate units, such as heavy rain. These events frequently caused high damage to the tree and other plant collections. These are expected to be taken into a consideration by the CBG operator and management in order to forecast and mitigate the risks of future plant collection losses.